2019
DOI: 10.1007/s11262-019-01641-7
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic initiation factor 4A (eIF4A) during viral infections

Abstract: The helicase eIF4A is part of the cellular eIF4F translation initiation complex. The main functions of eIF4A are to remove secondary complex structures within the 5′-untranslated region and to displace proteins attached to mRNA. As intracellular parasites, viruses regulate the processes involved in protein synthesis, and different mechanisms related to controlling translation factors, such as eIF4A, have been found. The inhibitors of this factor are currently known; these substances could be used in the near f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 69 publications
(81 reference statements)
0
18
0
Order By: Relevance
“…Among the different components, the eukaryotic translation initiation factor 4F (eIF4F) complex has been identified as being important for HEV replication. This complex is known to be involved in the cap-dependent translation and replication of several viruses (reviewed in [56]). In this context, an RNA interference-based loss-of-function study showed that components of the eIF4F complex are required for efficient HEV replication, while known negative regulatory factors of this pathway limit viral RNA synthesis [57].…”
Section: Viral Rna Replicationmentioning
confidence: 99%
“…Among the different components, the eukaryotic translation initiation factor 4F (eIF4F) complex has been identified as being important for HEV replication. This complex is known to be involved in the cap-dependent translation and replication of several viruses (reviewed in [56]). In this context, an RNA interference-based loss-of-function study showed that components of the eIF4F complex are required for efficient HEV replication, while known negative regulatory factors of this pathway limit viral RNA synthesis [57].…”
Section: Viral Rna Replicationmentioning
confidence: 99%
“…In human breast adenocarcinoma cells, inhibition of eIF4A blocks cell cycle progression at the G1/S phase transition, likely through loss of Cyclin D1, Cyclin D2 and Cdk6, and induces apoptosis, in part, by inhibiting translation of BCL2. However, the main influence of eIF4A on cell cycle progression is contributed at the level of the translation initiation process [ 113 ]. Also, eIF4A is crucial for the translation of viral IRES mRNAs [ 114 ].…”
Section: Rna Helicases In the Regulation Of Cell Cyclementioning
confidence: 99%
“…Many viral mRNAs contain highly structured 5′-UTRs, suggesting that eIF4A inhibitors may block viral replication [ 21 ]. Indeed, Grünweller and collaborators found that silvestrol, at low nanomolar concentrations that are not toxic to cells, blocks viral mRNA translation and viral replication of Ebola virus and MERS-CoV in cells [ 6 , 7 ].…”
Section: Antiviral Activities Of Flavaglines Mediated By Eif4amentioning
confidence: 99%
“…The importance of eIF4A during viral infections tends to be virus specific. In fact, viruses can either use it or not use it at all, or they may alternate between requiring and not requiring the eIF4A protein [ 21 ]. Several RNA viruses require eIF4A for the translation of their mRNAs, in particular those that are responsible for Ebola, chikungunya, hepatitis E, poliomyelitis, Zika fever, “hand, foot and mouth” disease, SARS, MERS and COVID-19 (recently reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation